Exposure to cigarette smoke affects endometrial maturation including angiogenesis and decidualization. (11th January 2021) - Kida, Naoko; Nishigaki, Akemi; Kakita‐Kobayashi, Maiko; Tsubokura, Hiroaki; Hashimoto, Yoshiko; Yoshida, Aya; Hisamatsu, Yoji; Tsuzuki‐Nakao, Tomoko; Murata, Hiromi; Okada, Hidetaka
Abstract: Purpose: To elucidate the effects of cigarette smoking on human endometrial maturation for reproductive function, the authors examined the in vitro effects of cigarette smoke extract (CSE) on angiogenesis and decidualization in primary human endometrial stromal cells (ESCs). Methods: Endometrial stromal cells were cultured with CSE and/or estradiol‐17β (E2 ) and medroxyprogesterone acetate (MPA). The mRNA, protein levels, and protein secretion of the angiogenic factors and decidual specific factors were assessed using real‐time polymerase chain reaction, Western blot analysis, and enzyme‐linked immunosorbent assay, respectively. Decidualization was also monitored by the changes in cellular morphology. Results: Endometrial stromal cell proliferation substantially decreased after dose‐dependent treatments with CSE at concentrations above 1%, whereas cell death was induced at treatment concentrations above 1% CSE. Treatments above 0.025% CSE led to increased vascular endothelial growth factor mRNA through hypoxia‐inducible factor‐1α accumulation. CSE concentrations at 0.01% and 0.025% increased the prolactin expression levels after treatment with E2 and MPA, whereas 0.1% and 0.25% CSE concentrations suppressed prolactin. Similar tendencies were observed in cellular morphology and other decidual specific factors. Conclusion: These results suggest that exposure to cigarette smoke affects endometrial appropriate maturation including the processes of angiogenesis and decidualization in the reproductive system.